Effect of cavitation treatment on the chemical composition of coal tar - Fengyun, Ma.; Baikenov, M.I.; Amerkhanova, Sh.K.; Shlyapov, R.M.; Uali, A.S. (Allerton Press, Inc., 2011)
The effect of a cavitation attack in the presence of pseudohomogeneous catalyst additives on the chemical composition of primary coal tar was studied. It was found that, upon the introduction of metal salts into coal tar, they underwent reduction followed by sulfidization; the resulting iron and nickel sulfides were nearly spherically shaped.